Intracoronary Administration of Drugs in Clinical Practice - Salo, Sergii V.; Shumakov, Valentyn O.; Gavrylyshyn, Andrii Yu.; Levchyshyna, Olena V.; Shpak, Sergii S. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Intracoronary administration of drugs allows to achieve the fastest possible effect in interventional cardiology. This allows to avoid all the biological filters of the body and achieve the required concentration of the active substance at the injection site. Also, given the local action, systemic side effects are nearly absent. The aim. To study the literature data of the leading countries of the world in the field of intracoronary drug administration. To analyze the experience of different centers on the use of various medications in the treatment of the phenomenon of distal microembolization. Results. One of the first drugs administered intracoronary was streptokinase for the treatment of acute myocardial infarction. After that, it became clear that this method of delivering drugs is possible and can be used. With the beginning of the treatment of acute coronary syndromes by stenting, one of the possible complications arose in the form of no-reflow. At the same time, realizing that this is a local problem, they began to use the possibility of intracoronary administration of drugs to treat this phenomenon. The main advantage of this method is quick response to drug administration. Today, the drugs of choice in the treatment of no-reflow are verapamil, adenosine, nitroprusside, adrenaline. On the other hand, probably the most common drug that is administered intracoronary is nitroglycerin. It is used as a vasodilator in the event of spasm of the coronary arteries. Subsequently, it has been recommended to deliver drugs via a microcatheter or aspiration catheter to achieve even more selective effect in the area of the affected vessel, and this also minimizes drug loss due to coronary reflux into the aortic sinuses while usinga guiding catheter. Work is also underway on the use of intracoronary insulin in acute coronary syndrome in order to reduce the area of damage in myocardial infarction. It is also very promising to study the introduction of stem cells directlyinto the myocardium through a microcatheter in order to regenerate the myocardium after a heart attack. Conclusions. Intracoronary administration of drugs allows to achieve the maximum effect in the shortest possible time. Today, many drugs can be used in this way, starting from the treatment of the phenomenon of distal microembolization and ending with myocardial regeneration after myocardial infarction.